The late Pleistocene-early Holocene rails (Gruiformes: Rallidae) of Laguna de Tagua Tagua Formation, central Chile, with the description of a new extinct giant coot. (December 2020) - Alarcón-Muñoz, Jhonatan; Labarca, Rafael; Soto-Acuña, Sergio
Abstract: Rallidae, which includes coots, crakes and moorhens, is one of the most speciose families among the Gruiformes. This family exhibits a pattern of diversification that has involved significant episodes of regional expansion and speciation resulting in the presence of members of this group in every continent with the exception of Antarctica. In this work, we describe the diversity of fossil rallids from late Pleistocene-early Holocene deposits of the Laguna de Tagua Tagua Formation located in central Chile. We report the presence of the extant taxa, Fulica armillata, Fulica rufifrons, Fulica cf. F. rufifrons, Fulica cf. F. ardesiaca and Pardirallus sanguinolentus, and also identify a large new extinct coot, Fulica montanei sp. nov. represented by three left tarsometatarsi. Fulica montanei corresponds to the first extinct rallid recorded in the Quaternary of South America. The most remarkable feature of the tarsometatarsus of Fulica montanei is their large size, which falls in the range of the extant Andean species Fulica cornuta and the extinct Fulica prisca from New Zealand. An autapomorphic combination of characters observed in the tarsometatarsi also supports the erection of a new species. These rails coexisted with extinct megafauna, as well as small and medium-sized vertebrates and, presumably, with humans, constituting a faunal assemblage with no analogous today. Fulica montanei probably became extinct during the late Pleistocene-early Holocene. Highlights: The rallid diversity of central Chile from the late Pleistocene-early Holocene is described in detail for the first time. A new bird species, Fulica montanei sp. nov. is described. Fulica montanei is the first well-documented extinct coot species from the Quaternary of South America.